A concurrent dual‐band LNA for noninvasive vital sign detection system. Issue 2 (February 2014) - Iyer, Brijesh; Pathak, Nagendra P.
ABSTRACT This article illustrates a pseudomorphic‐high electron‐mobility transistor 2.44‐/5.25‐GHz concurrent dual‐band low‐noise amplifier for noninvasive human vital sign detection using a standard hybrid microstrip integrated technology process. A novel dual‐band DC bias network is proposed to operate over 2.44‐/5.25‐GHz. Input and output impedance matching networks are designed using double open‐circuited shunt‐stubs. This allows simultaneous matching of arbitrarily different complex impedance (say of transistor) to standard 50‐Ω impedance at any two desired frequencies, while rejecting a wide‐band between them. The fabricated circuit exhibits gain of 7.15 and 7.80 dB, and noise figures of 4.34 and 4.69 dB at two desired frequency bands, respectively. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:391–394, 2014